ANTIBACTERIAL ACTIVITIES OF NELUMBO NUCIFERA EXTRACTS - Yucharoen, Raenu; Chaichana, Orathai; Srisuksomwong, Pawalee (Life Sciences and Environment Journal, 2024)
Pathogenic bacteria that pose a risk to human health can be transmitted through contaminated food. While antibiotics are commonly employed to eliminate these bacterial pathogens, their extended use often results in the development of antibiotic resistance. Thus, it is imperative to explore and evaluate the antibacterial properties of alternative agents derived from natural extracts. This research was to evaluate the antibacterial activity of extracts derived from the stamen and pistil of Nelumbo nucifera. The extracts were prepared using ethyl acetate and ethanol as solvents and were subsequently tested for their ability to inhibit the growth of eight bacterial subspecies: Escherichia coli, Salmonella Typhimurium, Bacillus cereus, Staphylococcus aureus, Serratia marcescens, Pseudomonas aeruginosa, Aeromonas hydrophila, and Proteus vulgaris. The assessment was conducted using the agar well diffusion method. The result showed that the pistil of N. nucifera extracted with ethyl acetate at a concentration of 500 mg/mL had the highest antibacterial activity. The inhibition of B. cereus was 29.33 ±0.58 mm. The stamen of N. nucifera extracted with ethyl acetate at a concentration of 500 mg/mL showed highest antibacterial activity against B. cereus with inhibition zone at 17.00 ±1.00 mm. Moreover, the ethyl acetate extract of pistil of N. nucifera showed highest antibacterial activity against B. cereus with MIC of 62.5 mg/mL and MBC of 250 mg/mL. In addition, the analysis of phenolic content using high performance liquid chromatography (HPLC) in ethyl acetate extracts from pistil part found that amount quercetin content had 147.18±15.91 µg/g of sample.